2020
DOI: 10.1016/j.vaccine.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the out of sight antigens of SARS-CoV-2 to design a candidate multi-epitope vaccine by utilizing immunoinformatics approaches

Abstract: Highlights The vaccine is composed of immunodominant regions of SARS-CoV-2 non-structural proteins. Also, the functional region of the spike protein is incorporated in the vaccine construct. The final vaccine construct contains multiple CD8+ and CD4+ overlapping epitopes Also, it contains multiple IFN-γ inducing, linear and conformational B cell epitopes. It forms significant interactions and stable complex with TLR-4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 118 publications
11
73
1
Order By: Relevance
“…The physicochemical properties of the vaccine, including instability index, grand average of hydropathicity (GRAVY), molecular weight, theoretical pI (isoelectric point), aliphatic index, and in vivo and in vitro half-life, were investigated using the ProtParam online server (http://web.expasy.org/protparam/) [38]. The immunodominant epitopes of SYCP1 and ACRBP antigen (C1) were used in the multiepitope vaccine [39], and the SARS-CoV-2 multi-epitope vaccine candidate (C2) [40] was used as positive control for comparing the polyvalent construct's properties. For predicting proteasomal processing, the NetChop (http://tools.iedb.org/netchop/) was used [38].…”
Section: Prediction Of Physicochemical Properties and Proteasomalmentioning
confidence: 99%
See 2 more Smart Citations
“…The physicochemical properties of the vaccine, including instability index, grand average of hydropathicity (GRAVY), molecular weight, theoretical pI (isoelectric point), aliphatic index, and in vivo and in vitro half-life, were investigated using the ProtParam online server (http://web.expasy.org/protparam/) [38]. The immunodominant epitopes of SYCP1 and ACRBP antigen (C1) were used in the multiepitope vaccine [39], and the SARS-CoV-2 multi-epitope vaccine candidate (C2) [40] was used as positive control for comparing the polyvalent construct's properties. For predicting proteasomal processing, the NetChop (http://tools.iedb.org/netchop/) was used [38].…”
Section: Prediction Of Physicochemical Properties and Proteasomalmentioning
confidence: 99%
“…Solubility is a vital physiochemical property for protein expression and, as a result, manufacturability. Proteins with insufficient hydrophilicity may have a substantial impact on their expression, efficacy, and manufacturability [40]. Furthermore, after overexpression in E. coli, the peptide solubility likelihood was 0.753713.…”
Section: Molecular Modeling Of Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also demonstrated the influential role of TLR4 in inducing immune responses against coronavirus [ [99] , [100] , [101] ]. Consequently, TLR4 was selected as the immune receptor for molecular docking in the present study, such as studies by Yang et al [ 102 ] and Safavi et al [ 103 ]. The molecular docking analysis showed that our vaccine has the ability to bind TLR4 and induce a strong immune response.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the importance of pre-existing and induced SARS-CoV-2-specific CD8+ and CD4+ T cell responses for immune protection in mild SARS-CoV-2 infection. Since then, studies suggested the inclusion of specific peptides to elicit T cell response in vaccine design and in silico analysis of SARS-CoV-2 proteins has detected candidate epitopes specific for protective T CD4+ or CD8+ and B responses with low risks of allergy or autoimmunity (17)(18)(19)(20) . In fact, approved vaccines induce T cell response in addition to the production of neutralizing antibodies for immunization against SARS-CoV-2 (21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%